PENGARUH PEMBERIAN PUPUK KASCING TERHADAP KETERSEDIAAN NITROGEN PADA BERBAGAI JENIS TANAH DAN SERAPAN NITROGEN OLEH PAKCOY (Brassica rapa L.) - Tiffani Nur Aisyah Hanafi; Eko Amiadji Julianto; Lelanti Peniwiratri (Jurnal Tanah dan Sumberdaya Lahan, 2023)
Nitrogen is a primary macro nutrient needed by plants and has an important role in plant growth. Regosols, Latosols, and Grumusols are soils that have the potential as a medium for plant growth, with different characteristics and levels of productivity and are constrained by soil nitrogen. Application of nitrogen-rich vermicompost as an alternative to overcome the problem of the three soils. The research aimed to determine the available nitrogen content and nitrogen absorption of pakcoy by adding vermicompost on Regosols, Latosols, and Grumusols. The research used a split-plot design with the main plot in the form of soil types (T1 = Regosols, T2 = Latosols, and T3 = Grumusols) and a subplot in the form of a dose of vermicompost fertilizer (K0 = 0 t ha-1, K1 = 10 t ha-1, K2 = 20 t ha-1, and K3 = 30 t ha-1) so there are 12 treatments and repeated three times. The results showed that the application of vermicompost to Regosols, Latosols, and Grumusols increased total N, available N, organic carbon, cation exchange capacity, plant height, fresh weight, dry weight, plant N, and plant N uptake. The dose of vermicompost 20 t ha-1 was the optimum dose for the parameter of N availability.